Indicators of athletes` effectiveness as a basis of team tactical training in women epee fencing - Zadorozhna, O.; Pityn, M.; Hlukhov, I.; Stepanyuk, S.; Kharchenko-Baranetska, L.; Drobot, K. (Trends in Sport Sciences, 2020)
Introduction. The work studied the indicators of athletes` effectiveness in women epee fencing and the opportunity of their implementation into tactical training. According to the current researches, tactical training in team fencing is not substantiated. Aim of Study. This study aimed to compare the indicators of athletes` effectiveness of the world`s top-8 women epee fencers during the season 2015-2016 in individual and team competitions and to substantiate the possibility of their use in tactical training. Material and Methods. We have recruited 8 coaches in fencing. They had to rank the components of tactical training (directions, means, methods, control tests, indicators of athletes` effectiveness). Then we analyzed the protocols and video recordings of top-8 epee fencers during the season 2015- -2016 (321 bouts in individual and 207 - in team events). To estimate their effectiveness in individual and team events we used several indicators (total number of bouts, the number of won bouts, defeats, draws, and their pattern). Results. Despite the indicators of the athletes` effectiveness are high in both individual and team competitions, the ratio between them is different. Six out of eight athletes showed higher effectiveness in individual events. The difference between those indicators in individual and team performances ranged from 10.27% to 22.12%. Only two athletes performed more successfully in team matches. The difference between the indicators of their effectiveness was 7.80 and 7.05%, respectively, in favor of team competitions. Conclusions. According to the indicators of athletes` effectiveness, tactical training should be based on the use of the role models of athletes. Each role model illustrates the ability to realize athletes` potential in an individual and team standings. The role models are the following: "universal fighters", "individual fighters", "team fighters", "individual fighters with team potential".